The Effects of Defatted Organic Red Jasmine Rice Bran Extract on Sun Protection Products - Thongtan, Dr. Jiraporn (Journal of Food Health and Bioenvironmental Science, 2018)
The effects of defatted organic red jasmine rice bran extract (DRBE) on sun protection properties were evaluated. Three formulations of sun protection products were studied as followed; two formulations consisted of oil in water emulsion and another formulation was gel emulsion and stability test was applied in all formulations. The results showed that DRBE at 1 μg/mL had antioxidant activity of 91.64% and IC50 of 64.02 μg/mL. The extract had the highest antioxidant stability of 88.12% when stored at 4o C. Furthermore, the effects of DRBE on sun protection factor (SPF) was found to have an effect on enhancing the sunscreen values on all three formulations, in which SPF values increased from 2.86 to 4.39. The highest SPF value of 4.39 was obtained for gel emulsion. Hence, the SPF values of these three formulations were claimed for medium protection and water resistance properties for 2 hour maximum. The gel emulsion showed the lowest reduction of SPF value at 0.08 and 0.2, respectively, after stored at room temperature for 30 and 60 days. These results demonstrated that DRBE boosted the SPF value and it can be potentially used as SPF stabilizer.